Resor Wisata Bambu Di Pekanbaru Dengan Pendekatan Arsitektur Modern (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru is one of the developing city, the tourist who come to Pekanbaru has given some effect to the development of tourism facilities. The regional tourist resort has a primary function as accomodation with excellent tourism facilities with artificial tourist attractions and sights of nature. Tourism resort area with tourism attraction bamboo plants and materials can attract tourist because the lack of utilization as aesthetics and building material. This tourism resort area has 5 Ha by applied Architecture Modern as themes that can improve the aesthetics of bamboo material. Architecture modern have been applied at the tropical climate that makes it possible to develop the concept in this tourist resort further by applying the concept of Ecomodern. Every building in this area become one of tourism attraction so do bamboo solar panel area also. With 1.7 m2 as building area has build with major facilities as a venue cottages and restaurant, relaxation and souvenir center as support facilities. Application of the principle of Modern Architecture in every building, following the architectural style of Mies Van Der Rohe as a reference and applying the concept of Ecomodern as a response to the tropical climate in Pekanbaru.Keyword: Resort, Tourism, Bamboo, Modern, Ecomodern, Mies Van Der Rohe.